1996
DOI: 10.1063/1.360909
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous (Mo, Ta, or W)–Si–N diffusion barriers for Al metallizations

Abstract: M-Si-N and M-Si ͑MϭMo, Ta, or W͒ thin films, reactively sputtered from M 5 Si 3 and WSi 2 targets, are examined as diffusion barriers for aluminum metallizations of silicon. Methods of analysis include electrical tests of shallow-junction diodes, 4 He ϩϩ backscattering spectrometry, x-ray diffraction, transmission electron microscopy, scanning electron microscopy, and secondary-ion-mass spectrometry. At the proper compositions, the M-Si-N films prevent Al overlayers from electrically degrading shallow-junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…However, most of them suffer from thermal instability of effective work function after high temperature annealing [1][2][3][4]. The use of amorphous ternary M-Si-N (M =Ta, Mo, W) as a diffusion barrier for Al or Cu metallization has been previously studied [5][6], and the use of TaSi X N Y as a metal gate electrode candidate has been recently reported [7]. In this report, MOS capacitors with reactively sputtered Mo X Si Y N Z (Y>X; Z=1-(Y+X)) metal gates deposited with various N concentrations were examined.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them suffer from thermal instability of effective work function after high temperature annealing [1][2][3][4]. The use of amorphous ternary M-Si-N (M =Ta, Mo, W) as a diffusion barrier for Al or Cu metallization has been previously studied [5][6], and the use of TaSi X N Y as a metal gate electrode candidate has been recently reported [7]. In this report, MOS capacitors with reactively sputtered Mo X Si Y N Z (Y>X; Z=1-(Y+X)) metal gates deposited with various N concentrations were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, when temperature is applied to the substrate we observed the formation of fcc-TiO crystalline phase. Diffraction peaks identification demonstrates that it corresponds to cubic titanium oxide fcc-(TiO) 3.38 (JADE PDF-card # 75-0310). Also, Fig.…”
Section: The Indentation Modelmentioning
confidence: 99%
“…24,25 Especially, ternary diffusion barriers of the TM-Si-N (TM = Ta, Mo, or W) type have shown superior performance in Cu metallization. [26][27][28][29][30] There have also been intensive studies on Ti-Si-N films using various deposition and annealing methods. [31][32][33][34][35] It has been shown that the diffusion capability and resistivity Deposition Characteristics of Ti-Si-N Films Reactively Sputtered from Various Targets in a N 2 /Ar Gas Mixture variation of this film are mostly influenced by the film composition.…”
Section: Introductionmentioning
confidence: 99%